Revision of the genus Alloplasta Förster, 1869 (Hymenoptera, Ichneumonidae, Banchinae) from Japan - Watanabe, Kyohei (Zootaxa, 2022)
Japanese species of the genus Alloplasta Förster, 1869 are revised. A total of nine species are recorded from Japan, including four new species, A. breviterebra sp. nov., A. japonica sp. nov., A. satana sp. nov. and A. septentrionalis sp. nov. and three species, A. brevipetiolaris Kang & Lee, 2020, A. kuslitzkii Kasparyan, 2007 and A. subgrisea Kasparyan, 2007, newly recorded from Japan. Amersibia longipetiolaris Uchida, 1952 is newly synonymized under A. nigripes (Meyer, 1930) (syn. nov.). A key to Japanese species of this genus is proposed.